Direct seeding with different furrow openers: changes in properties of a South Brazilian latosol (oxisol) and crop yields (Revista de Ciências Agroveterinárias, 2018)
The mechanisms of seeding machines to cut the mulch, mobilize the topsoil and deposit the seeds in the furrows modify soil properties and interfere in crop growth. This study sought to evaluate the effects of furrow openers and scarification on the attributes of a South Brazilian latosol (Bruno – oxisol) and crop yields. The treatments were: double disc furrow opener (DD); shovel type furrow opener (S); shoe type furrow opener (SH); and scarification followed by double disc furrow opener (SC+DD). Samples were collected at 0-10, 10-20 and 20-40 cm and evaluated for soil physical (bulk density, total porosity, macro and microporosity), chemical (pH, Ca, Mg, K and P) and organic carbon content. The normality of data was tested, and the analysis of the variance was performed (F test, p
Keywords: agricultural implements; seeding machine; soil physics